Phytochemical analysis of ionic liquid-Graviola (Annona muricata) fruit extract and its acute toxicity on zebrafish early-life stages - Daddiouaissa, Djabir; Amid, Azura; Ahmad, Syahida; M. Elnour, Ahmed A. (Malaysian Society For Molecular Biology & Biotechnology, 2020)
Annona muricata, commonly known as soursop and Graviola, is a member of the Annonaceae family. Some of its phytochemicals were reported to have a neurotoxicity effect causing neurodegenerative diseases. However, different parts of this tree have been used for ages in traditional medicine due to their biological activities, such as anti-inflammatory, antimicrobial, antioxidant and anticancer effects. This study aimed to qualitatively screen the crude ionic liquid-Graviola fruit extract (IL-GFE) phytochemical composition, assess its acute toxicity and determine the lethal concentrations using zebrafish (Danio rerio) embryos. IL-GFE contains acetogenins, alkaloids, phenols, terpenoids, tannins and flavonoids. Acute toxicity effects of IL-GFE on zebrafish embryos were observed from 24 to 120 hours of post fertilisation (hpf). The survival rate, LC50, sublethal endpoints and effect of IL-GFE on the heart rate of zebrafish larvae were assessed. Results showed that the lethal concentration (LC50) of the crude IL-GFE was 173.45 μg/mL. Interestingly, no significant changes on the morphology of the treated zebrafish were observed at a concentration of 125 μg/mL. However, the heart rate of zebrafish larvae at 96 hpf was significantly decreased by 33.76% after treated with crude IL-GFE at 125 µg/mL (119.00 ± 4.72 beats/min) as compared to the untreated group (179.67 ± 4.66 beats/min). This preliminary finding showed that crude ionic liquid-Graviola fruit extract and its phytoconstituents might have the potential to be developed as a food supplement or herbal product. However, further tests need to be conducted to evaluate its medicinal properties and adverse effects on organisms of higher orders.